Introduction of a Transparent Assessment procedure to Develop Presentation Skills in Geography Students - Perera, M.O; Ranasinghe, E.M.S (My University, 2007)
Numbers of Arts graduates are increasing annually, while their effectiveness in the job market is questioned. Developing their generic skills, such as presentation skills, will enable them to partly overcome these impressions. Students should be made active learners by making the process of learning motivational and interesting to them (Biggs 1999). When assessment is transparent, students are motivated to achieve their best performance. If performance of the students related to their skills is being evaluated through a transparent assessment procedure, students are made aware of, and motivated to acquire, such skills. Geography Special degree students participate in learning activities to develop their skills. They take a compulsory course unit which includes two presentations that are evaluated. However, until 2004 their presentation skills were not evaluated and the assessment procedure was not disclosed to them. In 2004, the marking scheme for assessing the presentations was reviewed and was introduced to the students prior to the assessment. The results showed a significant improvement in student performance at assessment, as well as of their presentation skills. A feedback questionnaire on the presentations showed that 47% of students ‘strongly agreed’ and 38% ‘agreed’ that “the awareness of the criteria for the assessment helped me to do this presentation in a more organized and more confident way”. We also interviewed a sample of 15 students (23% out of 67) who graduated in 2005 and 2006 to evaluate how their acquired presentation skills had facilitated their present employment. Forty percent of the selected students had joined the private sector and 60% were employed in the public sector. The majority of the students (60% to 100%) agreed that they had developed specific skills such as confidence and time management through these presentations. 87% of students felt that practice in talking in front of an audience had facilitated facing job interviews.